Sifat Termal Karbon Aktif Berbahan Arang Tempurung Kelapa - Tamado, Daniel; Budi, Esmar; Wirawan, Riza; Dwi, Haryo; Tyaswuri, Anggie; Sulistyani, Erlinda; Asma, Esty (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2013)
It has been observed a thermal property of activated carbon which made from coconut shell with DSC (Differential Scanning Calorimeter) apparatus in various atmosphere. The thermal properties of activated carbon are closely related to the pores number and sizes of particle. The early parameters which determined to that are depending on a production processes, such as temperature of pyrolisis process, Pressure (on compaction process) and forming of powder on milling process. Besides of those points, the thermal properties are also can be reviewed from temperature glass of that. DSC analysis result showed that there is a temperature peaks different on the each atmospheric conditions (Gases contained in atmosphere) so that we can determine an ideal condition of activated carbon in any utilities Keywoards : activated carbon, thermal property, differential scanning calorimeter.